The Optimization of Pharmacy Waiting Time Using the Lean Healthcare Method - Nuraini, Novita; Wijayanti, Rossalina Adi (P3M Politeknik Negeri Jember, 2023)
The waiting time for prescription services at dr. M. Suherman Clinic, a primary healthcare clinic with pharmacy services, did not meet the standard. It was about 15 minutes for the maximum waiting time for non-concoction prescriptions and 30 minutes for concoction medicines. A pre-liminary study of 100 patient visits in a day revealed that 15 non-concoction prescriptions and 20 concoction prescriptions exceeded the waiting times standard. It explicated the inefficiency in pharmacy services. The purpose of this research was to make the waiting time for pharmacies became more efficient. This research used lean healthcare method by using fishbone and 5M management elements. The data were collected by interviews, observation, and brainstorming. This study found that waiting time for pharmacy services approximately 36 minutes, with the Non-Value-Added ratio 56,7 %. It is concluded that the condition of pharmacy services had been inefficient. The units which contributed most waste were polyclinics and pharmacies. This research will produce a definite solution using the brainstorming method. The clinics need to standardize the deadline for doctors to input prescriptions, update the medical drug formulary, add new computers and drug blenders, add the number of staffs as human resources, and rearrange the clinic rooms.